Beyond the Classroom: The Implications of School Vouchers for Church Finances - Hungerman, Daniel M.; Rinz, Kevin; Frymark, Jay (The Review of Economics and Statistics, 2019)
Governments have used vouchers to spend billions of dollars on private education; much of this has gone to religiously affiliated schools. We explore the possibility that vouchers could alter the financial outcomes of religious organizations that are operating schools and thus have an impact on the spiritual, moral, and social fabric of communities. Using a data set of Catholic parish finances from Milwaukee, we show that vouchers are a dominant source of funding for many churches. Vouchers appear to offer financial stability for congregations as voucher expansion prevents church closures and mergers. However, voucher expansion causes significant declines in church donations and church revenue from noneducational sources.